O Programa Saúde na Escola : análise da implementação de uma política pública de educação - Costa, Roosevelt Rodrigues da (2013)
This research was focused social policies in Brazil with educational interface, in particular the Health Program at school - PSE, which is presented as an intersectoral policy coordination between health and education guided through a process of ongoing formation activities education in schools proposing interventions in the organization of the pedagogical work of schools and teachers. Developed a research on the concepts of education, training and organization of pedagogical work of this policy, explaining that the historical project is concatenated. Thus, we analyze the contradictions between such concepts advocated in the documents that served as the empirical sources (presidential decree establishing the PSE and instructional manuals) and the possibilities of its development in the reality of school education. This analysis was developed with dialectical historical approach by reference to the class struggle, as a category that helps us understand reality by contradiction, given that historically the capitalist mode of production forge a fragmented human existence into classes that are expressed the contradictions between capital and labor, bourgeoisie and proletariat, which are, in turn, expression of exploitation of man by man. In this context, we stand for an analysis from the perspective of the working class, used the method of dialectical historical materialism. For its realization we developed the following scientific problem: what are the links between the design and determinations of permanent training and the design of the school´s pedagogical work organization and teacher contained in the School Health Program? We conducted a theoretical research (literature) having bounded to analyze the Presidential Decree 6,286 / 2007 and the 2011 PES instructional manuals and 2013, which contain concepts of training and organization of pedagogical work. We use as technical content analysis guided by the analytical categories: Reality and Possibilities. With the research argue that the theoretical concepts (educational and pedagogical) present in that educational materials and in-person training and distance proposals do not consider the socio-historical determinations and contradictions concerning the theory and practice of concrete reality in which will be operationalized intervention revealing thus not critical theoretical trends, that is, they are not linked to the needs of working. These determinations and contradictions are explained, (1) the proposal of continuing education and distance as the main route of capillarity; (2) the dichotomy between theory and practice in performing their activities; (3) the impracticability of the principle of intersectionality with planning and implementation of joint activities between education and health professionals within schools; and (4th) in funding, which has the health network as a resource management route. In addition, (5) consider that the PSE has come up with a proposal to meet the needs of adolescents and youth who are in school, however, the questions (problems) by the program are not connected to the real needs of the school, but needs to reach demands of public health, with the school as privileged locus. Thus, falls on the school and on teachers, responsibilities that are not genuinely yours.